Intergenerational and intragenerational preferences in a developing country to avoid climate change - Alvi, Shahzad; Salman, Verda; Bibi, Fazal Un Nisa; Sarwar, Naima (Frontiers in Psychology, 2023)
Inter-generational and intra-generational approaches to climate change take into account the actions taken by the current generation to maintain or improve the climate, which is advantageous to both the present and future generations. Future generations profit most from climate-friendly initiatives, but at the expense of current generations, who benefit to a lesser extent. Agents' self-interest impedes the management of shared resources in "the tragedy of the commons," a phrase frequently used to refer to global environmental challenges; defection benefits the individual while the consequences of defection are shared by society. Using three alternative time horizons to reflect inter- and intra-generational discounting, we examine how groups of human subjects respond to the issue of preventing hazardous climate change under alternative settings that reflect choices under the presence or absence of motivation and with or without income endowment, along with social pressure and the opportunity to learn with time. We conducted two group experiments framed around climate change where participants could choose to cooperate for a noble cause: tree plantations. Its rewards are delayed by several years and probably a few decades (inter-generational discounting), where future generations will be the big beneficiaries. There were two more options: the first one delayed the reward by one week, and the second was delayed by seven weeks (intra-generational discounting). We found that inter-generational discounting was high when the groups had free will and motivation. Our experimental results show that having more money doesn’t play a significant positive role in long-term climate sustainability; it does, but not as much as motivation and free will do.